Rolling with the punches: An examination of team performance in a design task subject to drastic changes. (January 2015) - McComb, Christopher; Cagan, Jonathan; Kotovsky, Kenneth
Abstract : Designers must often create solutions to problems that exhibit dynamic characteristics. For instance, a client might modify specifications after design has commenced, or a competitor may introduce a new technology or feature. This paper presents a cognitive study that was conducted to explore the manner in which design teams respond to such situations. In the study, teams of undergraduate engineering students sought to solve a design task that was subject to two large, unexpected changes in problem formulation that were introduced during solving. High- and low-performing teams demonstrated very different approaches to solving the problem and overcoming the changes. The results indicate that there may exist a relationship between problem characteristics and fruitful solution strategies. Highlights: High- and low-performing teams varied in the methods they used to solve a problem. Low-performing teams showed extended periods of high divergence. High-performing teams developed simple final design solutions. High-performing teams also extensively searched specific areas of the space.